KEANEKARAGAMAN JENIS TUMBUHAN DI CAGAR ALAM KAKENAUWE DAN SUAKA MARGASATWA LAMBUSANGO, PULAU BUTON SULAWESI TENGGARA - Tahan Uji (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
Study on richness diversity plants in Kakenauwe Nature Reserve and Lambusango Game Reserve had been conducted. One hundred and seventy species of Spermatophyta, 12 species of Pteridophyta and 24 species of Bryophyta are collected from this area. One hundred and four species of Spermatophyta and 6 species of Pteridophyta are reported as potential species of plants. The largest group is timber (32 species) and other is ornamental plants (24 species), medicinal plants (17 species) and edible fruits (13 species). This study also reported that Orthorrhynchium phyllogonioides is recorded as “new record” of Bryophyta collections in Sulawesi.